KORELASI TRANSAKSI E-MONEY DAN PERTUMBUHAN JUMLAH UANG BEREDAR (M2) DI INDONESIA 2010-2019 - Siska Azkia; Fakhruddin Fakhruddin; Chenny Seftarita; Ferayanti Ferayanti (Universitas Teuku Umar, 2021)
This study aims to determine the correlation of e-money transactions and the growth of the money supply (M2) in Indonesia 2010-2019. The variables used in this study include the volume of e-money transactions and the money supply (M2). In this study using descriptive quantitative methods. The analytical tool used is Granger Causality where the processing uses the Eviews9 software application, with secondary data consisting of monthly data. The results of this study indicate that the variable M2 seems to significantly affect e-money (5.E-09) because it is smaller than the alpha value of 10% and the e-money variable also significantly affects M2 (0.0004) So it can be concluded that only the e-money variable and M2 which has a two-way causality. This means that the value of M2 transactions in the past can affect the value of e-money in the present, and vice versa, the value of e-money transactions in the past can affect the value of M2 in the present in the 2010-2019 period. So it can be said that people in Indonesia have understood the use of electronic transactions (e-money) or non-cash transactions. In addition, Indonesia is a developing country with a large population, so that when there is a change or an innovation it will quickly develop so that it supports various aspects that are applied. Keywords: E-Money, Jumlah Uang Beredar (M2), Granger Causality.